Proving the Role of Farmers’ Expectation and Income in Determining their Acceptability towards CSR Program: Evidence from East Kalimantan, Indonesia - Irham, Irham; Suhadi, Imam; Mulyo, Jangkung Handoyo; Jamhari, Jamhari (AGRARIS: Journal of Agribusiness and Rural Development Research, 2026)
Despite the growing implementation of CSR programs in agricultural communities, empirical evidence on how farmers perceive and accept these interventions remains limited, particularly in developing countries. Understanding the determinants of farmer acceptance is essential for improving CSR program effectiveness and sustainability. This study aims to measure the level of farmer acceptance of Corporate Social Responsibility (CSR) programs and to determine the key factors that influence it. The SERVQUAL model was used to analyze farmers' expectations and acceptance levels across five dimensions: reliability, tangibility, responsiveness, empathy, and assurance. Multiple linear regression analysis was applied after confirming normality, linearity, and multicollinearity assumptions to examine the relationships among farmers' acceptance and the independent variables, including expectation, income, age, education, land size, experience, household size, and organization. This study was conducted in Kutai Timur Regency, Kalimantan Timur Province, through a survey of 114 farming households receiving CSR assistance, selected using a multistage sampling technique. Research results indicate that farmer acceptance of CSR programs is relatively low. The study found that expectations and income were significant positive drivers of farmer acceptance, while social interaction and training had a significant negative effect. It is recommended that CSR program managers prioritize initiatives that demonstrably increase farmers' income and focus on long-term, sustainable benefits, particularly in the oil palm and animal husbandry sectors, to enhance program acceptability and effectiveness. This study introduces a novel SERVQUAL‑based framework to assess farmers’ acceptance of agricultural CSR programs and generate practical insights for program design and implementation.